CONCEPT OF “MONEY” IN THE MINDS OF NATIVE ENGLISH SPEAKERS (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
The concept of MONEY occupies a pivotal role in the cognitive and societal frameworks of native English speakers. This thesis delves into how MONEY is perceived and understood, exploring its multifaceted nature through linguistic, psychological, and cultural lenses. It examines how various aspects—ranging from language and cultural values to psychological impacts and societal influences—shape the understanding and representation of MONEY among native English speakers.